2007
DOI: 10.1186/1471-2199-8-66
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of nucleolin leads to nucleolar disruption, cell cycle arrest and defects in centrosome duplication

Abstract: Background: Nucleolin is a major component of the nucleolus, but is also found in other cell compartments. This protein is involved in various aspects of ribosome biogenesis from transcription regulation to the assembly of pre-ribosomal particles; however, many reports suggest that it could also play an important role in non nucleolar functions. To explore nucleolin function in cell proliferation and cell cycle regulation we used siRNA to down regulate the expression of nucleolin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
208
4
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 195 publications
(228 citation statements)
references
References 61 publications
13
208
4
3
Order By: Relevance
“…4), as it was shown to be the case after overexpressing a dominant negative form of ninein. 14 This nucleation delay is neither a consequence of NCL silenced cells accumulating in G2, 29 since the rate of microtubule nucleation is unchanged in G2 compared to G1. 39 Since purified nucleolin did not favor microtubule nucleation by itself (data not shown), we concluded that nucleolin might act as an activator of microtubule nucleation when bound to centrosomal gTuRC, thereby playing a role in the acquisition of mature markers on immature centrioles.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…4), as it was shown to be the case after overexpressing a dominant negative form of ninein. 14 This nucleation delay is neither a consequence of NCL silenced cells accumulating in G2, 29 since the rate of microtubule nucleation is unchanged in G2 compared to G1. 39 Since purified nucleolin did not favor microtubule nucleation by itself (data not shown), we concluded that nucleolin might act as an activator of microtubule nucleation when bound to centrosomal gTuRC, thereby playing a role in the acquisition of mature markers on immature centrioles.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 The presence of these supernumerary structures in interphase cells was analyzed in regards to PCM components like g-tubulin (Figs. 4A-E and K), pericentrin (Figs.…”
Section: Nucleolin Silencing Leads To Amplification Of Centriole Immamentioning
confidence: 99%
See 3 more Smart Citations